Conservação do patrimônio educativo e as possibilidades de uso como material didático para o ensino de química - Palma, Raquel Santos [UNIFESP] (2020)
The assets that constitute the cultural heritage of the school, this study highlights the set of educational scientific objects. A research survey that answers three main questions: about why, for what and for whom preserves these materials; and how it would be possible to involve the school community in the preservation of educational heritage. In order to answer these questions, you can find out through the specialized literature in the area of ​​Education and Heritage or the work of researchers dealing with the safeguarding of educational heritage and analyze which conservation actions are most used for this type of material and how they suffer maintaining these actions continuously at school. Thus, a research is characterized as a qualitative study, compared to the literature review. As a general objective, a proposal was made for an orientation booklet designed to guide the school community through its content and to act with the preservation of the educational heritage, in addition to indicating some possibilities of using these objects as didactic material for teaching Science Nature, in particular the teaching of Chemistry. The content of the guidance book was based on the information collected by the literature review. Thus, the initial work presents a research methodology. No following items discuss the process of capturing objects by Brazilian schools to understand these objects as a source of information and to understand how historically they have been forgotten over time. Subsequently, some conceptual aspects that involve the Theory of Conservation are presented and then a brief discussion about the procedures for the conservation of the school collection is presented, seeking to relate as conservation methods with specificities of educational medical objects. Finally, to present the objects as an alternative pedagogical resource for Nature Science classes in perspective of the Heritage Education methodology and as final considerations.